Notes to field reports contributed by Francis L. Moore, spring 1984 - Moore, Francis L.et al (1984)
Notes to field reports were contributed by Francis L. Moore, spring 1984. These notes provided details of sightings of eight species in his separate field notes list. Birds covered and their locations were: Snowy Egret near Albion, Ruddy Shelduck at Sweet Marsh, Northern Goshawk near Cedar Falls, Peregrine Falcon at Sweet Marsh, Common Tern at Cedar Lake, Northern Saw-Whet Owl in Mills County, Summer Tanager near Waterloo, and Henslow's Sparrow at Hayden Prairie. Other observers were Robert K. Myers, Russell Hays, W. Ross Silcock, and Barbara L. Wilson. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed/flatbed